Cross species transferability of microsatellite markers from Anas platyrhynchos to Peruvian Muscovy Duck Cairina moschata domestica - Acuña Rodriguez, Wendy (2020)
Peruvian Muskovy duck (Cairina moschata domestica) is one of the most economically important species in human nutrition. Duck species form complex genetic groups which are difficult to recognize, thus the use microsatellite markers (SSRs) identified already in Anas platyrhynchos (related species), represents a very attractive option for its cheapness and usefulness for solving issues related to conservation of genomic diversity, gene flow and hybridization between population. The main goal of this work was to evaluate the degree of polymorphism (PIC) and the transferability of 24 SSRs identified for A. platyrhynchos to C. moschata domestica. In this study, DNA collected from wing feathers was extracted using the chloroform-isoamyl alcohol method. SSRs were constructed with an additional 19 bp sequence (M13 tail) and 6-FAM, VIC, NED and PET fluorophores were used for their labeling. The amplified fragments were visualized on 2% agarose gels and separated by capillary electrophoresis in an automatic ABI 3130XL sequencer. Results showed 7 SSR with high PIC value (PIC> 0.5) and the CMO211 marker expressed in a smaller molecular size that the one used as reference. In conclusion, we showed that 75% of the SSR designed for A. platyrhynchos were transferable to C. moschata domestica as well as we found only 7 SSR highly informative, thus we proved that SSR are highly useful for detecting polymorphisms in related species and improved the Peruvian populations of Muskovy ducks.